PENERAPAN HERMENEUTIK DI GBI ROCK SATELIT MONANG-MANING DENPASAR - Gabriel Ruth Wijaya; Roy Pieter; Edwin (Diegesis : Jurnal Teologi, 2022)
This study aims to describe the understanding of the cell group leaders about the hermeneutical principle, the understanding of the cell group leaders about the hermeneutical method; and the application of hermeneutics by the cell group leaders at GBI ROCK Monang-Maning Satellite Denpasar. This research is a qualitative research with the object of research is the application of hermeneutics at GBI ROCK Monang-Maning Satellite Denpasar. The collection techniques used were observation, documentation study and online interviews with 10 respondents. The data were analyzed by means of data condensation, data presentation and conclusion drawing. Testing the validity of the data using the credibility test and data reliability test. The results showed that the cell group leaders understood general hermeneutic principles, but still did not understand the specific hermeneutic principles. In terms of the hermeneutic method, the results showed that not all complex shepherds understood the hermeneutic method. In terms of application, the research results show that even though they understand the principles and methods of hermeneutics, there are still cell group leader who do not apply them in practice so that there are still misinterpretations in the sermons.